2017
DOI: 10.1038/ijo.2017.76
|View full text |Cite
|
Sign up to set email alerts
|

The impact of protein quantity during energy restriction on genome-wide gene expression in adipose tissue of obese humans

Abstract: Based on gene expression changes, we concluded that consumption of normal protein quantity compared with high-protein quantity during ER has a more beneficial effect on inflammation-related gene expression in WAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…An 8-wk trial of an energy-restricted high (30% energy) compared with a low (15% energy) protein diet indicated that high compared with low protein, and meat protein in particular, but not plant or fish protein, increased a score that included CRP, IL-6, TNF-α, and PAI-1 concentrations (27). Another 12-wk trial of protein intake in the context of 10% energy restriction, this one in overweight, older participants, indicated that a high-protein diet (1.7 g · kg body weight –1 · d –1 ) compared to a normal-protein diet (0.9 g · kg body weight –1 · d –1 ) induced differential expression in 530 genes in white adipose tissue, notably a downregulation in expression of genes linked to immune cell infiltration, adaptive immune response and inflammasome in the normal-protein group, but not the high-protein group (46). However, a 6-wk ad libitum high animal compared with high plant protein (30% energy) diet in overweight or obese individuals with nonalcoholic fatty liver disease and type 2 diabetes showed no differences in IL-6 or MCP-1 between diets, a decrease in IL-18 only in the high animal protein group, and a decrease in TNF-α only in the plant protein group (24).…”
Section: Discussionmentioning
confidence: 99%
“…An 8-wk trial of an energy-restricted high (30% energy) compared with a low (15% energy) protein diet indicated that high compared with low protein, and meat protein in particular, but not plant or fish protein, increased a score that included CRP, IL-6, TNF-α, and PAI-1 concentrations (27). Another 12-wk trial of protein intake in the context of 10% energy restriction, this one in overweight, older participants, indicated that a high-protein diet (1.7 g · kg body weight –1 · d –1 ) compared to a normal-protein diet (0.9 g · kg body weight –1 · d –1 ) induced differential expression in 530 genes in white adipose tissue, notably a downregulation in expression of genes linked to immune cell infiltration, adaptive immune response and inflammasome in the normal-protein group, but not the high-protein group (46). However, a 6-wk ad libitum high animal compared with high plant protein (30% energy) diet in overweight or obese individuals with nonalcoholic fatty liver disease and type 2 diabetes showed no differences in IL-6 or MCP-1 between diets, a decrease in IL-18 only in the high animal protein group, and a decrease in TNF-α only in the plant protein group (24).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a genome-wide association study [ 72 ] explored the effects of protein quantity in diets during energy restriction on OR gene expression in white adipose tissue (WAT). This study revealed that high-protein energy restriction (HP-ER) diets resulted in distinct gene expression changes compared to normal-protein energy restriction (NP-ER) diets.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, patients with a higher BMI also showed improvements in odor identification tasks upon intranasal insulin administration [ 86 ]. Another study indicated that the presence of insulin in the olfactory bulb could be connected with the process of satiation and the pathogenesis of obesity [ 72 ]. GLP-1 agonist treatment decreases the olfactory preference for sweet- and fat-enriched food [ 87 ] and improves olfactory sensitivity and odor-induced right parahippocampal activation [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the molecular basis of the individual response to interventions is still poorly understood. For instance, dietary or physical exercise interventions have shown changes in the metabolome (van Dijk et al, 2012; Pellis et al, 2012; Zeevi et al, 2015) but are frequently unable to identify changes in the transcriptome (Van Bussel et al, 2017; Fazelzadeh et al, 2018; ten Haaf et al, 2018). Also, the time-scale needed to investigate responses to interventions remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These metabolic and caloric challenge tests are regarded upon as novel potential biomarkers of health (van Ommen et al, 2014; Stroeve et al, 2015) recording the phenotypic flexibility of individuals within minutes to hours of the test triggering acute and complex stress responses (energy fluxes, oxidative and inflammatory stress, apoptosis etc.). Hence, there is a need to monitor the response not only by traditional health markers but also at the molecular level (Van Bussel et al, 2017; Catoire et al, 2012).…”
Section: Introductionmentioning
confidence: 99%